Perbandingan Pengelolaan Pengeluaran Keuangan Negara Indonesia dengan Singapura - Fajriah, Rabi'ah; Hartanti, Fitri; Anggraini, Dini; Nurcahyati, Siti (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2024)
Indonesia's state expenditure is allocated to central government expenditure and transfers to regions as regulated in Law No. 17/2003 on State Finance. Meanwhile, Singapore's state financial expenditure management is regulated under the Singapore Financial Procedure Act, with state expenditure focused on infrastructure development, education, and quality public services. However, in the management of state financial expenditure there are still problems such as budget leakage, corruption, and inefficiency in the management of state expenditure, as well as a lack of transparency and accountability in the planning and implementation of state expenditure. This study aims to compare the state financial expenditure of Indonesia and Singapore by looking at the type of expenditure, the classification of state expenditure and the budgeting and expenditure mechanism. This research uses normative juridical methods. The results of this study are the management of Indonesia's financial expenditures are divided into two main types, namely routine expenditure and development expenditure. While Singapore's state financial expenditure is divided into two, namely operating expenditure and development expenditure. The difference between these two countries lies in the expenditure system, the state expenditure system in Indonesia includes two methods of paying bills to the state, namely: Direct Payment Method and Through Money Supply. Meanwhile, the Singapore Government also applies a line-item budgeting system with a consistent balance budget policy. The similarity is that both countries include development expenditure in the type of state expenditure.